Public Awareness of Gastric Cancer Symptoms and Risk Factors: A Cross-Sectional Study from Al-Zawia, Western Libya - Mufida Khetresh; Ekraam Amir; Hana Alazraq; Wejdan Bzaga; Assala Mjahed; Mohammed Shatty; Alayham Albshti (Khalij-Libya Journal of Dental and Medical Research, 2025)
Gastric carcinoma continues to be the fourth leading cause of cancer-related mortality globally. Disparity in incidence rates across different geographical regions has been ascribed to environmental factors predominantly, rather than genetic determinants. This study aims to evaluate the level of awareness about the symptoms and risk factors of gastric carcinoma among the general population in Libya, and to identify socio-demographic factors associated with varying levels of awareness. Data for this descriptive cross-sectional study were collected from the general population in Zawia, using a pretested, validated questionnaire. The collected data were analyzed by using SPSS software. The sample comprised 435 individuals, with a slightly higher proportion of females (55.4%) compared to males (44.6%). The majority (59%) were under the age of 40. Overall, 42.7% of participants demonstrated a moderate level of knowledge regarding gastric cancer. The most commonly recognized risk factors were alcohol consumption (82.5%) and smoking (74.9%), while the most frequently identified warning sign was abdominal pain (74%) followed by a loss of weight (71.3%). A statistically significant association was observed between educational level and awareness (p < 0.001). Moderate levels of knowledge regarding the risk factors and warning symptoms of gastric cancer were recorded in most of the population in Zawia. especially concerning lifestyle-related risk factors like smoking and alcohol use. However, a knowledge gap persists, particularly for less obvious risk factors (e.g.; partial gastrectomy, blood group, and vitamin B 12 deficiency).